Design of using chamber system based on electrical impedance spectroscopy (EIS) to measure epithelial tissue - Paulo C. Calvo; Oscar Campo; Cristian Guerra; Santiago Castaño; Faruk Fonthal (Sensing and Bio-Sensing Research, 2020)
This work aims to propose a Ussing chamber system based on electrical impedance spectroscopy (EIS) for measuring impedance in epithelial tissues. The proposed method is composed of two functional parts: Ussing chambers (UC) where the tissue under test is located, and the other is a homemade electrical impedance spectroscopy system. The impedance spectroscopy system architecture uses a sine wave generated by a direct digital synthesizer (DDS) with a frequency range from 1 Hz to 102 kHz, a current source in Howland configuration, and an instrumentation stage that allows applying the four electrodes configuration. The designed system was tested with Eleutherodactylus johnstonei adult frog Epithelial tissue, as well as Cole-Cole models, Real and imaginary, and measured impedances were used to find the transfer function parameters employing a genetic algorithm.